THE ROLE OF MANIFESTATIONS OF THE JADIDIST MOVEMENT IN THE FORMATION OF POLITICAL CULTURE AMONG YOUTH (American Journal of Research in Humanities and Social Sciences, 2022)
This article examines the socio-political views of the Jadids, the first socio-political movement that embarked on the path of struggle for national independence in Turkestan was the movement of Jadidism. The Jadids proclaimed their main goal to build a secular democratic state by reforming its economic, political and cultural life, working out their own way of introducing the peoples of Central Asia to the achievements of world civilization.